Kiai Nur Hakim Pasir Wetan: Penyebaran Tarekat Syatariyah dan Gerakan Tarekat Akmaliyah Di Banyumas - Rosadi, Arif; Chamadi, Muhamad Riza (MOMENTUM : Jurnal Sosial dan Keagamaan, 2023)
In the 19th century the Shatariyah tariqa was the most popular order in Banyumas. The figure who spread the Shatariyah tariqa was Kiai Nur Hakim. However, so far it is not known which points or areas are the place of distribution. This study seeks to find the distribution points of the Shatariyah tariqa in Banyumas. In addition, it also discusses the Akmaliyah tariqa movement in Banyumas. The focus of the research is on the figure of Kiai Nur Hakim, namely his role in the tariqa which lies in efforts to spread the Shatariyah tariqa in Banyumas and its political movement, namely the Akmaliyah tariqa movement. There are two formulations of problems in this study: First, where are the areas where the distribution of the Shatariyah tariqa in Banyumas carried out by Kiai Nur Hakim, second how the Akmaliyah terakat movement takes place. The research method uses historical methods, through several stages, namely heuristics (data collection), verification (source criticism), interpretation (interpretation), and historiography (historical research). The result of the study was that the Syatariyah tariqa was spread in several areas in Banyumas, namely in the villages of Pasir Wetan, Cikakak, and Sokaraja District. In the Akmaliyah tariqa movement, Kiai Nur Hakim failed to achieve his goal of establishing a sultanate state because the strength of the members of the Akmaliyah tariqa was not comparable to the strength of the Dutch government.